TASK - BASED LANGUAGE TEACHING (TBLT) CAN IMPROVE STUDENTSâ WRITING ABILITY - Sholihah, Umi (MAGISTRA, 2013)
The purpose of this article is to examine the uses of TBLT can improve studentsâ writing ability. Besides that, this article also gives evidences of the research which is designed to identify the strengths and the weaknesses of the implementation of TBLT in improving studentsâ writing ability. The research findings of this research imply that TBLT is very effective. The implementation of TBLT improved the studentsâ writing ability. It gives the chance to the students to explore their ideas and to choose their own words, and encourages students to be active learners. It could raise the studentsâ participation in writing class and could enhance the studentsâ writing ability. In TBLT, the teacher has a lot of opportunities to develop various activities. TBLT also made the students able to make a composition using appropriate vocabulary, correct grammar, mechanics, content, and organization. Finally, this article is expected to be useful for other researchers more particularly those who are interested in conducting a similar research. Key Words: writing ability, Task â Based Language Teaching (TBLT), improving, classroom action research.